2013
DOI: 10.1016/j.virol.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of the bacteriophage T4 terminase docks on the prohead portal clip region during DNA packaging

Abstract: Bacteriophage ATP-based packaging motors translocate DNA into a pre-formed prohead through a dodecameric portal ring channel to high density. We investigated portal–terminase docking interactions at specifically localized residues within a terminase-interaction region (aa279–316) in the phage T4 portal protein gp20 equated to the clip domain of the SPP1 portal crystal structure by 3D modeling. Within this region, three residues allowed A to C mutations whereas three others did not, consistent with informatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 47 publications
3
36
1
Order By: Relevance
“…However, this fitting positions the ATPase domain ring distal to the capsid, whereas the nuclease domains interact with portal (Fig. S4E), an interaction that has been observed recently (10). Thus, our revised TerL ring model is a different arrangement than that previously proposed.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…However, this fitting positions the ATPase domain ring distal to the capsid, whereas the nuclease domains interact with portal (Fig. S4E), an interaction that has been observed recently (10). Thus, our revised TerL ring model is a different arrangement than that previously proposed.…”
Section: Resultsmentioning
confidence: 64%
“…Although many ATPase rings are asymmetrical during function (12, 37), we assume fivefold symmetry for simplicity. Regardless, most ringed ATPase structures were first modeled as symmetrical assemblies (32,38), and these models were refined later to show asymmetry during function (9,10,12,37). After docking of the ATPase ring, we used the full-length crystal structure of T4-TerL (8) to orient a homology model of the P74-26 nuclease domain, which results in minimal steric clashes between the two domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The portal’s grip is then released while the motor’s grip is retained, resulting in relaxation of the DNA back to the B form and entry of ~2 bp into the capsid. A number of observations on the T4 motor are consistent with this model (83, 98, 99). For instance, intercalating compounds tightly bound to DNA are expelled during DNA translocation, which might be due to DNA crunching.…”
Section: Dna Translocationmentioning
confidence: 54%
“…These studies are consistent with the presence of a portal-binding site in the central region of gp17. On the other hand, fluorescence resonance energy transfer studies suggested that a fluorescent probe attached to the C terminus of gp17 is closer in distance to the N terminus of the portal than is another fluorescent probe attached to the N terminus of gp17, which led to the prediction of an opposite orientation (83). In phage SPP1, the C-terminal domain but not the N-terminal domain of TerL (gp2) bound to the prohead portal (38).…”
Section: Dna Translocationmentioning
confidence: 99%